2016
DOI: 10.1007/978-3-319-39225-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Core-Periphery Communication and the Success of Free/Libre Open Source Software Projects

Abstract: Part 1: Full PapersInternational audienceWe examine the relationship between communications by core and peripheral members and Free/Libre Open Source Software project success. The study uses data from 74 projects in the Apache Software Foundation Incubator. We conceptualize project success in terms of success building a community, as assessed by graduation from the Incubator. We compare successful and unsuccessful projects on volume of communication by core (committer) and peripheral community members and on u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…The periphery is important to FLOSS projects [21], [26], [44]. As the periphery is largely episodic, we suggest that episodic participation is also important for FLOSS projects.…”
Section: The Importance Of Episodic Contributorsmentioning
confidence: 75%
See 1 more Smart Citation
“…The periphery is important to FLOSS projects [21], [26], [44]. As the periphery is largely episodic, we suggest that episodic participation is also important for FLOSS projects.…”
Section: The Importance Of Episodic Contributorsmentioning
confidence: 75%
“…Early studies of the FLOSS phenomenon made a distinction between core and peripheral developers. Even today, many studies use this dichotomy to characterize FLOSS community members [44].…”
Section: Terminologymentioning
confidence: 99%
“…Thus, the type of software engineering work carried out is an important factor characterizing the corresponding social network structures. In terms of development mailing lists, non-core participants may post as many messages as core participants [25], but this observation does not generalize to all cases [34], including the case studied. Although coordination requires communication, coordination tends to result in different network structures than communication required for other work (or leisure) activities.…”
Section: Cve Coordination Through a Mailing Listmentioning
confidence: 91%
“…The definitions for such developers differ. For instance, some authors have identified core developers with a cutoff point for vertex degrees [57,110], while others have relied on documents about developer responsibilities and commit accesses [21,25]. In the present context the relevant social network core is composed by the MITRE affiliates.…”
Section: Social Network and Communication Metricsmentioning
confidence: 99%
“…A prior version of this paper was presented at the IFIP Working Group 2.13 OSS2016 Conference [26]. The current version includes additional data analysis done to identify peripheral members who became committers and their contributions, and additional changes to the methods, findings and discussion sections.…”
Section: Acknowledgementsmentioning
confidence: 99%